Finitary and Artinian-Finitary Groups over the Integers ℤ - Wehrfritz, B.A.F. (Український математичний журнал, 2002)
In a series of papers, we have considered finitary (that is, Noetherian-finitary) and Artinian-finitary groups of automorphisms of arbitrary modules over arbitrary rings. The structural conclusions for these two classes of groups are really very similar, especially over commutative rings. The question arises of the extent to which each class is a subclass of the other.